Perkembangan Asuransi Kesehatan Swasta di Indonesia Tahun 2012-2016 - Sari, Kurnia (UI Scholars Hub, 2017)
Total private insurance spending in 2015 is about 3.9% of Indonesia’s health expenditures. Although it is not considerably high, the information about private health insurance in Indonesia is still limited. This review is aimed to provide an overview of the private health insurance company growths in Indonesia. The number of private insurance company does not grow significantly, while the number of membership tends to fluctuate in the last 5 years, even it is tend to decrease for non life insurance category. Sums assured tend to rise until 2014, then stagnant for the next period. The amount of premium received by the company and claims to be paid (claim ratio) is considerably increase. It could not be denied that government program for achieving the universal health coverage is a threat to private insurance